Senior high school students' responses to graphical and mathematical representation items: The case of kinematics - Amaliah, Nur Utami; Hasanati, Alvi; Latifa, Baiq Rizkia Ayu; Kusairi, Sentot (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
This research aims to investigate and compare students’ responses in solving physics problems about kinematics concepts. The students’ responses cover the conceptual understanding as overall performance, representational abilities, and students’ response patterns.This research is a non-experimental survey research with thequantitative-descriptive approach. The research samples consisted of 56 students determined by the purposive sampling technique. The research instrument was adapted from the Force Concept Inventory (FCI) in Physport Assessmentwhich has been validated. The students’ responses were analyzedusing descriptive statistics to measure the average and standard deviation. Students’ answers were also grouped according to the type of representation and pattern of presentation in percentages. The results showed a significant difference between the tenth-grade students’ and eleventh-grade students' understanding of the Kinematics concept. Furthermore, the students found it easier to answer mathematical representation questions rather than graphical representation questions.